Oxygen consumption (resting and after treatment), immune variables and hormone levels of Rhinella jimi (anura:bufonidae) collected in 3 different periods from Caatinga, Brazil - Carla Bonetti Madelaire (PANGAEA, 2021)
To understand the possible interactions between steroid hormones (androgens [AN] and corticosterone [CORT]), metabolism, and immunity during fluctuations of environmental resource, we studied the interactions between field steroid plasma levels (AN and CORT), field immune parameters (plasma bacterial killing ability [BKA], swelling response to phytohemagglutinin (PHA - 20 ug/ml) injection), resting metabolic rate (RMR), rates of oxygen consumption after PHA injection, and parasite load in 3 periods A) within the rainy season (N = 25 in March 21 to April 15, 2013); B) during a breeding event (N = 5; February 15 to 18, 2014); and C) during the dry season (N = 8 collected in September 2 to 14, 2013) of a toad (Rhinella jimi) from a highly seasonal environment (the Brazilian semi-arid, Caatinga, 5°30 extquotesingle43 extquotesingle extquotesingleS. 36°36 extquotesingle18 extquotesingle extquotesingleW). Considering that air temperature also can affect metabolism and immune response, we also provide the air temperature registered during each oxygen consumption measure and during the development of the swelling response to the PHA injection. The rates of oxygen consumption (RMR and after treatment) were measured using positive-pressure, flow-through respirometry (Withers, 1977). The air was pumped through the chambers at 100 mL.min^-1^ using a Flowbar Multichannel – 8 pump system (Sable Systems; Henderson, NV, USA). RMR consisted of lowest value of oxygen consumption for whole 5 minutes. Oxygen consumption after the treatment is the highest value ~ after PHA (V,O2PHA) and saline (V,O2Saline) injection. The metabolic cost to PHA (MC~PHA~) and saline (MCsaline) injections were calculated by subtracting the RMR from their respective V,O2PHA and V,O2saline. Circulating plasma levels of AN and CORT were quantified using enzyme immunoassay kits (Testosterone ELISA Kit 582701; Corticosterone ELISA Kit 500655) from Cayman Chemical (Ann Arbor, MI).